Instability and failure characteristics of surrounding rock of water drenching roadway in thick coal seam - Jia, Ce; Li, Sheng; Fan, Chaojun; Luo, Mingkun; Yang, Zhenhua; Yang, Lei; Pu, Ziang (Frontiers in Earth Science, 2022)
Aiming at the water drenching problem in the roof of transport roadway 2,606 of the Zhangcun coal mine, the instability and failure law of the drenching roadway was studied by borehole peephole, soaking water softening test and numerical simulation in this study. It is found that the relation between compressive strength, elastic modulus, tensile strength and moisture content is a negative exponential function. Subsequently, the Fish language was used to embed the functional relationship between mechanical parameters of surrounding rock in the roadway and moisture content into Flac3D software to simulate the failure law of surrounding rock under different moisture contents. The influence of moisture content on the surrounding rock is ordered as roof > two sides > floor. Through the comparison between borehole peeping and plastic zone, the roof water content is obtained by inversion. The results provide a reference basis for the selection of the surrounding rock support method for drenching roadway in thick coal seam.